Diversity and function of arbuscular mycorrhizal fungi in host species succession - Gomide, Plínio Henrique Oliveira; Santos, José Geraldo Donizetti dos; Siqueira, José Oswaldo; Soares, Cláudio Roberto Fonsêca Sousa (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effects of pre-cultivation of different plant species and of arbuscular mycorrhizal fungi (AMF) on the sporulation, colonization and growth of Urochloa cultivated in succession, under greenhouse conditions. Plants were grown in pots containing a sterilized mixture of very clayey Oxisol and washed river sand at a 2:1 ratio (v/v). A completely randomized experiment with nine treatments and ten replicates was initially tested: six mycotrophic plant species; a non-mycotrophic species (forage turnip); a treatment with Urochloa decumbens and a control treatment without plants. All treatments received a mixture of eight AMF species. The mycorrhizal colonization and sporulation of Urochloa decumbens, by means of AMF propagules obtained from the remaining mycotrophic and non-mycotrophic species, was evaluated. There was difference among the host plants in terms of percentage of mycorrhizal colonization and total production of spores, and five out of the eight isolates studied were identified. Glomus clarum was the dominant AMF in most of the treatments, followed by Scutellospora heterogama and G. etunicatum. Pre-cultivation plant species had no effect on the AMF diversity; the fungus species were determinant for the composition of the fungal isolates.